Chest Wall Deformities - Saxena, Amulya K.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2017)
This comprehensive work offers detailed state of the art information on the changing paradigms in the evaluation, diagnosis, clinical investigation, and treatment of chest wall deformities. The chapters reflect the shift towards conservative and minimal access treatment options, and the combination of concise descriptions and high-quality images provide the reader with a clear understanding of all relevant concepts. Diagnostic and imaging modalities are analysed in depth, and surgical procedures are explained step by step with the aid of clear, informative illustrations. Experts in the management of chest wall deformities from all over the world have contributed their experiences and approaches, making Chest Wall Deformities a unique book in the field and an ideal reference work for clinicians and surgeons.
GENERAL -- CLINICAL INVESTIGATIONS -- HISTOLOGICAL EVALUATIONS -- ASSOCIATED CONDITIONS -- PECTUS EXCAVATUM Minimal access repair -- Thoracoscopic aspects -- The Ravitch Procedure -- Willital-Hegemann procedure Minimal cartilage resection technique Free sternum turnover flap procedure -- Pectus correction using Kirschner wires -- Non-prosthetic surgical repairVacuum treatment -- Magnetic mini-mover procedure -- Macrolane -- Mesh repair procedure -- Metal-free open-repair procedure Nuss procedure in adult patients -- Recurrent pectus excavatum repair -- Free fat transplantation -- PECTUS CARINATUM -- Nonoperative management Dynamic compression system Radiographic markers Minimal invasive endoscopic repair -- Endoscopic Pectus Carinatum Repair Pectus carinatum repair Reactive pectus carinatum in patients treated for pectus excavatum -- OTHER CHEST WALL DEFORMITIES -- PLIER procedure for complex chest wall deformities -- Chest Wall Repair in Poland$1 (Bs Syndrome Asphyxiating Thoracic Dystrophy Sternal defects.s
Keywords: Medicine; Radiology; Surgery; Pediatric surgery; Medicine & Public Health; General Surgery; Pediatric surgery; Imaging / Radiology